Buddy, the first seeing eye dog - Moore, Eva; Bolognese, Don (New York Scholastic, 1996)
True account of the training and early work experiences of the German shepherd which became the first seeing eye dog in America
Hurg
5
Keywords: Buddy (Dog) -- Juvenile literature; Guide dogs -- Training of -- United States -- Juvenile literature